A new species of Sweltsa (Plecoptera: Chloroperlidae) from Sichuan Province of southwestern China - Dong, Wenbin; Cui, Jianxin; Li, Weihai (Zootaxa, 2018)
A new chloroperlid stonefly species, Sweltsa brevihamula sp. nov. from Sichuan Province of southwestern China is described and illustrated. We also provide a provisional key to the known Sweltsa males of China.